Integrated behaviour change intervention for sustainable community development: a KAP study of WASH in district Gujrat, Pakistan. (19th October 2022) - Afzal, Afzaal; Javed, Muqaddas; Jabeen, Tahira
Abstract: Behaviour change interventions are fundamental to achieve sustainability in communities through the identification of new, and strengthening the existing positive practices. It is considered central to the quest for a sustainable future and solves multidimensional community problems, which require large scale shifts in human behaviour with regard to their health, socio-physical activities and long held habits. In this context, the study examines the role of integrated behaviour change interventions for sustainable community development by exploring the direct and mediating impacts through knowledge attitude and practice (KAP) of water, sanitation and hygiene (WASH). The primary data was collected from district Gujrat (Pakistan) through stratified random sampling to explore the impacts of KAP of WASH and its relationship with child health and sustainable community development. The hypotheses of the study were tested with smartPLS software. Findings of the overall sample of the study have revealed that integrated behaviour change interventions have significant impacts on KAP, WASH practices in daily life, child health (CH) and sustainable community development (SCD). Furthermore, the relationships among variables are positively significant and have direct and mediating impacts on sustainable community development. HIGHLIGHTS: Integrated behaviour change interventions regarding water, sanitation, and hygiene for the improvement of child health and sustainable community development. Knowledge, attitudes, and practices of mothers on a domestic level in daily life and its relationship with community development. Water, sanitation, and hygiene work as mediation variables for achieving sustainable community development.